Iridium-Doped Manganese Oxide Nanosheets with Enhanced Pseudocapacitive Properties - Muramatsu, Keisuke; Saito, Ryota; Sugimoto, Wataru (Meeting abstracts (Electrochemical Society), 2024)
Atomically thin inorganic oxides, called nanosheets, are attractive electrode materials especially for electrochemical supercapacitors because of their large surface area and tunable composition. Birnessite-type manganese oxide nanosheets are one of the promising candidates because they possess pseudocapacitance associated with fast redox process in neutral electrolytes and electrochemical stability at wide potential range. One of the significant drawbacks for manganese oxide nanosheets-based capacitive electrodes is its poor conductivity. Doping manganese oxides with other transition metals is known as an effective method to increase the electronic conductivity as well as the specific capacitance. 1–2 We have reported the preparation of a new solid solution, iridium-doped birnessite-type manganese oxide K-(Mn 1– x Ir x )O 2 ( x = 0, 0.05, 0.1). 3 Interestingly, K-(Mn 1– x Ir x )O 2 exhibits enhanced redox-related pseudocapacitance in aqueous Li 2 SO 4 with unusual Mn 4+ /Mn 3+ redox where the peak-to-peak potential difference decreased with increasing the amount of doped Ir. Here, we report successful exfoliation into iridium-doped manganese oxide nanosheets ((Mn 1– x Ir x )O 2 (ns)) and its charge storage capabilities. The parent layered oxide, K-(Mn 0.9 Ir 0.1 )O 2 , was prepared by coprecipitation method according to literature. 3 After proton exchange of K-(Mn 0.9 Ir 0.1 )O 2 and subsequent shaking in an aqueous tetrabutylammonium hydroxide solution, colloidal dispersion with a dark-green color was formed. Transmission electron microscopy and electron diffraction revealed the formation of crystalline nanosheets with the lateral size of several hundreds of nanometers. UV-vis spectrum of the dispersion of (Mn 0.9 Ir 0.1 )O 2 (ns) shows absorption peak at around 365 nm, which is blue-shifted from that at around 380 nm of non-doped MnO 2 (ns). These results indicate that the exfoliation of K-(Mn 0.9 Ir 0.1 )O 2 successfully proceeded while preserving the iridium in the manganese oxide framework. For electrochemical measurements, (Mn 0.9 Ir 0.1 )O 2 (ns) was composited with acetylene black (AB) as a conductive binder and the mixture was casted onto a glassy carbon electrode. Cyclic voltammetry in 1.0 M Li 2 SO 4 in the potential range of 0.6–1.2 V versus RHE shows the broadened but large redox currents associated with the Mn 4+ /Mn 3+ redox reaction. The specific capacitance of (Mn 0.9 Ir 0.1 )O 2 (ns)/AB at various scan rates is larger than that of MnO 2 (ns)/AB and less dependent on the scan rates. These changes are probably due to an improvement in the charge-transfer process of the Mn 4+ /Mn 3+ redox, which indicate that the strong electronic interaction between Mn and Ir was preserved even after exfoliation. (1) S.-J. Kim, I.Y. Kim, S.B. Patil, S.M. Oh, N.-S. Lee, S.-J. Hwang, Chem. Eur. J. , 2014 , 20 , 5132. (2) M. Nakayama, K. Suzuki, K. Okamura, R. Inoue, L. Athouël, O. Crosnier, and T. Brousse, J. Electrochem. Soc. , 2010 , 157 , A1067. (3) R. Saito, H. Tanaka, K. Teshima, D. Takimoto, S. Hideshima, and W. Sugimoto, Inorg. Chem. , 2022 , 61 , 4566.